Organizational Politics and Media Employee Performance during COVID-19 - Taha Shabbir; Abdul Sattar Khokar; Nabiha Khan; Arsalan Khan (Universitas Negeri Makassar, 2021)
Many people have spoken about organizational politics about corporate well-being. Employee performance is examined in the context of the COVID-19 epidemic as a result of high-performance work practices (training, empowerment, and incentives). The findings suggest that the chosen high-performance work practices of media employees during COVID-19 had a poor association. Having a negative association with performance nullifies the current evidence of empowerment. Public media administrators must design standard operating practices that take into account the current upheavals. Performance may be improved by using organizational resources and time in a manner that fosters trust between the employer and the employee. The links are examined in the context of the fourth industrial revolution. While studying high-performance work practices and media worker performance in a developing nation, this is a novel addition. The result shows a lack of trust among the media employees, which might lead to the abuse of authority. As a result, media organizations must put in place sufficient checks and balances before empowering their staff. Since the recent epidemic of COVID-19, employees may be more inclined to take advantage of the technology development.